The Importance of Nutrition Education to Change Mother's Knowledge and Behaviour in Achieving Adequate Nutrition for Toddler - Fitriyani, Poppy; Mulyono, Sigit; Handayani, Tri Widyastuti (Global Health Science Group, 2024)
The problem of undernutrition among toddlers is still a problem that cannot be resolved properly. The role of the family in overcoming the problem of undernutrition is very necessary because toddlers are dependent on nutritional requirements. Therefore, efforts are needed to overcome this problem by increasing the provision of appropriate nutritional education for toddlers so that toddlers avoid the problem of malnutrition. This research aims to determine the extent of the influence of providing nutrition education on mothers' knowledge and behavior in fulfilling nutrition for toddlers. The research design used a